REWAS 2016 Towards Materials Resource Sustainability - Kirchain, Randolph; Blanpain, Bart.; Meskers, Christina; Olivetti, Elsa.; Apelian, Diran; Howarter, John.; Kvithyld, Anne.; Mishra, Brajendra; Neelameggham, Neale; Spangenberger, Jeff.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Topics covered in this collection include the following: •Enabling & Understanding Sustainability - Ferrous & Non-ferrous Metals Processing •Understanding & Enabling Sustainability - (Rechargeable) Batteries •Enabling & Understanding Sustainability - Rare Earth Element Applications •Enabling & Understanding Sustainability - Building Materials & Slag Valorisation •Designing Materials and Systems for Sustainability •Understanding & Enabling Sustainability - Light Metals Recycling & Waste Valorisation •Understanding & Enabling Sustainability - Education Research Innovation I •Understanding & Enabling Sustainability - Education Research Innovation II + Electronic Equipment.
Keywords: Materials -- Analysis; Refuse and refuse disposal; Materials; Characterization and Analytical Technique; Waste Management/Waste Technology; Materials Engineering